Herpes simplex virus type 2 in sub-Saharan Africa and the potential impact of helminth immune modulation - Pillay, Roxanne; Naidoo, Pragalathan; Mkhize-Kwitshana, Zilungile L. (Frontiers in Cellular and Infection Microbiology, 2024)
Herpes simplex virus type 2 (HSV-2) and helminth infections are among the most widespread infectious diseases in sub-Saharan Africa (SSA). Helminths are known to modulate host immune responses and consequently impact the severity and outcomes of unrelated diseases, including allergies, autoimmune conditions, and infectious diseases. In this way, helminths may modulate essential immune responses against HSV-2 during co-infection and may alter susceptibility to and pathology of HSV-2. However, the epidemiology of STH/HSV-2 co-infections is understudied, and whether helminths influence the host immune response to HSV-2 is not well understood. In this perspective piece, we briefly examine the current knowledge on helminth immune modulation of important pathogens that are endemic to SSA, arguing that it is important to explore HSV-2 and helminth co-infections to elucidate potential interactions between HSV-2 and helminths. This is particularly relevant in SSA, where both pathogens are highly prevalent.